Efeitos do uso do solo sobre a vegetação: estudo de caso em inselberg no Cariri paraibano - Menezes, Marcelo Costa de (2016)
The Caatinga is a very important biome in the social, economic and environmental context, however is little valued, studied and poorly maintained. The main objective was to make a comparison of the structure and composition of trees - shrubs and cactuses between 3 areas of different land uses. The specific objectives were to make a phytosociological survey of the site and a bibliographic study of the use and importance of the species found. The methodology applied to the phytosociological survey consisted of marking 50 plots of 50 x 2 m, for a total of 0.5 hectares. Within the plots were identified all sized individuals tree, shrub, subshrubby and cacti, and measuring the height and the diameter at chest level of individuals (DBH> 2cm) in subjects with PAD <2cm were only measured height. ecological parameters of wealth were calculated number of individuals, frequency, dominance, diversity of Shannon - Wiener, Pielou evenness and importance value. The land use maps of the area were made with GIS data. To quantitatively compare the areas of different land uses, it was held the Shapiro-Wilk normality test and analysis of variance (ANOVA / unifactorial) or Kruskal-Wallis. Multivariate analysis was used of the main components (PCA) to verify structural differences in different areas. For flora similarity test was done by cluster analysis (cluster) by averaging method UPGMA group being made a qualitative and quantitative comparison with the Jaccard coefficients and Bray Curtis. The survey of the use and importance of the species was made a bibliographic reference. They were found in 2623 individuals in 82 species, 72 genera and 32 families. The families with the highest number of individuals and species were Fabaceae (16), Euphorbiaceae (11) and Cactaceae (5). The Tacinga inamoema species (K. Schum.) N.P. Taylor & Stuppy, Croton blanchetianus Baill.e Bauhinia cheilantha (Bong.) Steud stood out for having highest importance values. The land use maps of the area confirmed the progress of identified areas of very serious risk of desertification and also showed that forest fragment is currently one of the only in the city of Congo. There were statistical differences in different areas as the structure of the community according to the tste variance and PCA. The floristic similarity showed no differences in species composition in different areas of land use. 61 species were found to have obtained 11 kinds of uses, and the medical, construction and uses honey that stood out in the species. We conclude that the studied forest fragment is a priority for conservation because it is one of the only in the region, has razoálvel ecological diversity, contains useful species for the population, is home to species at risk of extinction due to misuse of land and contain species invasive. However, it is necessary to create a conservation unit that area and a management plan activities to develop socio-economic and environmental.